2011
DOI: 10.1111/j.1747-4949.2011.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs between Effectiveness and Efficiency in Stroke Rehabilitation

Abstract: There are trade-offs between effectiveness and efficiency during inpatient sub-acute stroke rehabilitation with respect to admission functional status and length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
1
31
0
1
Order By: Relevance
“…Greater neurological impairment 13 --(5) urinary incontinence, 14 23 (6) myocardial infarction 1 (7) longer 'stroke onset to admission into rehabilitation unit' time, 14 26 (8) longer 'admission to unit to start of rehabilitation' time, 14 (9) poor adherence to clinical practice guidelines, 17 (10) territory of stroke, 17 (11) orthogeriatric setting (as compared with a two-step model of orthopaedic surgery followed by transfer to a geriatric rehabilitation facility), 18 (12) (20) infarct (vs haemorrhage) stroke 26 and (21) shorter length of stay (LOS). 23 26 The independent predictors of REs/MRFS/RFG were supported by stroke (9 studies), post-hip-fracture arthroplasty (5 studies), elderly (1 study) and gait disorders (1 study).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater neurological impairment 13 --(5) urinary incontinence, 14 23 (6) myocardial infarction 1 (7) longer 'stroke onset to admission into rehabilitation unit' time, 14 26 (8) longer 'admission to unit to start of rehabilitation' time, 14 (9) poor adherence to clinical practice guidelines, 17 (10) territory of stroke, 17 (11) orthogeriatric setting (as compared with a two-step model of orthopaedic surgery followed by transfer to a geriatric rehabilitation facility), 18 (12) (20) infarct (vs haemorrhage) stroke 26 and (21) shorter length of stay (LOS). 23 26 The independent predictors of REs/MRFS/RFG were supported by stroke (9 studies), post-hip-fracture arthroplasty (5 studies), elderly (1 study) and gait disorders (1 study).…”
Section: Resultsmentioning
confidence: 99%
“…However, if the first functional measurement was performed many days after admission or the last functional assessment was performed many days before date of discharge, REy and RREy may be spuriously high if LOS was used in the denominator. Hence, it may be more accurate to use the number of days between the date of first and last functional measurement as the denominator for REy instead of LOS, as conducted by Koh et al 26 In fact, it was because Koh et al used time between first and last functional assessment in their study that they were able to demonstrate that LOS was an independent predictor of REy and not the result of statistical singularity arising from LOS being the denominator of REy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the factors related to prognosis of ADL in stroke and post-hip-fracture patients include: old age4, 5 ) , cognitive impairment4, 6 ) , and lower pre-rehabilitation functional status6,7,8 ) . Few reports have focused on the factors related to prognosis of ADL of elderly patients with acute medical illness9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Эти со стояния имеют неблагоприятные последствия: снижают качество жизни пациента и увеличивают нагрузку на членов его семьи, увеличивают расходы системы здравоохранения [7]. Сообщалось, что различные факторы способствуют неблагоприятному прогнозу в отношении функциональ-ной активности пациентов после инсульта, в их числе возраст [8][9][10], ухудшение физических функций до реаби-литации [11], когнитивные нарушения [8] и недержание мочи [9]. Через 12 месяцев после инсульта около 28% пациентов остаются зависимыми в таких сферах, как оде-вание, использование туалета и передвижение по поме-щению [12].…”
unclassified